Dominant factor determining the conduction-type of nitrogen-doped ZnO film - Li, L. (2014)
Nitrogen-doped zinc oxide (ZnO) film has been grown by molecular beam epitaxy. The as-grown sample showed p-type conduction with a hole concentration of 3.1×1017 cm−3. After an annealing process in O2 at 600 °C for 30 min, p-type conduction was still remained, and the hole concentration of the film decreased to 6.8×1016 cm−3. Secondary ion mass spectroscopy revealed that the concentration of both nitrogen and hydrogen decreased after the annealing process. It is demonstrated that the intrinsic compensation source has been decreased after the annealing process. Because the variation trend of the hole concentration in the ZnO:N film is opposite to that of hydrogen and intrinsic defects, but in good accordance with nitrogen, the extrinsically substituted nitrogen (NO ) should be the dominant factor that determines the conduction-type of the ZnO:N film.